2021
DOI: 10.2340/00015555-3872
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities of Prurigo Nodularis in Finland Between 1996 and 2019

Abstract: Table I. Demographics of the study population Characteristics Study population, n 306 Female/male, n 184/122 Age, years, mean ± SD (range) 68.6 ± 13.9 (18-96) Age at diagnosis, years, mean ± SD (range) 56.7 ± 15.1 (10-93) Smoking status, n (%) Yes, current/previous 69 (22.5) No or data not available 237 (77.5) SD: standard deviation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 14 publications
2
20
1
Order By: Relevance
“…18 In addition, our finding about depression and anxiety in LP patients is comparable to psychiatric morbidity overall among adult patients with another itching skin disease, prurigo nodularis, in Finland. 19 However, the prevalences in our study were not as high as in the recent meta-analysis. 17 This can arise, for example, from the different study design and the fact that the metaanalysis also included cases of pure oral LP, and those with oral LP have been described to have higher risk of depression than cases with cutaneous LP.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…18 In addition, our finding about depression and anxiety in LP patients is comparable to psychiatric morbidity overall among adult patients with another itching skin disease, prurigo nodularis, in Finland. 19 However, the prevalences in our study were not as high as in the recent meta-analysis. 17 This can arise, for example, from the different study design and the fact that the metaanalysis also included cases of pure oral LP, and those with oral LP have been described to have higher risk of depression than cases with cutaneous LP.…”
Section: Discussioncontrasting
confidence: 95%
“…Thus, there was more depression among LP patients than in general Finnish population (12.0% among those aged 45–54 years and 7.0% in those aged 55–64 years, respectively) 18 . In addition, our finding about depression and anxiety in LP patients is comparable to psychiatric morbidity overall among adult patients with another itching skin disease, prurigo nodularis, in Finland 19 . However, the prevalences in our study were not as high as in the recent meta‐analysis 17 .…”
Section: Discussionsupporting
confidence: 54%
“…A similar study in the USA showed that patients with prurigo nodularis had a higher burden of several cardiovascular, pulmonary and other systemic diseases than those with atopic dermatitis and those with psoriasis 28 . A study of 223 patients from Finland also found frequent cardiovascular, respiratory, psychiatric or endocrine comorbidities 29 . A Korean study found that prurigo nodularis was associated with chronic kidney disease (adjusted odds ratio 1·48), dyslipidemia (1·88), type 2 diabetes mellitus (1·37), arterial hypertension (1·50), autoimmune thyroiditis (2·43), non‐Hodgkin lymphoma (1·95) and atopic dermatitis (2·16) 30 …”
Section: Epidemiologymentioning
confidence: 91%
“…28 A study of 223 patients from Finland also found frequent cardiovascular, respiratory, psychiatric or endocrine comorbidities. 29 A Korean study found that prurigo nodularis was associated with chronic kidney disease (adjusted odds ratio 1Á48), dyslipidemia (1Á88), type 2 diabetes mellitus (1Á37), arterial hypertension (1Á50), autoimmune thyroiditis (2Á43), non-Hodgkin lymphoma (1Á95) and atopic dermatitis (2Á16). 30 Higher frequency and higher severity were shown in African Americans by comparison with other parts of the US population.…”
Section: Epidemiologymentioning
confidence: 99%
“…PN is accompanied by persistent itching and is thought to develop from repetitive scratching ( 5 ) in patients with chronic pruritus from various causes ( 6 ). Epidemiological studies have determined PN to coexist with chronic liver disease, HIV, and type 2 diabetes mellitus (DM), among other diseases ( 1 , 4 , 7 , 8 ), but the aetiological significance of the relationship is not known. An increased prevalence of PN has been observed in patients undergoing dialysis ( 9 , 10 ).…”
mentioning
confidence: 99%